Vortices capturing matter: a classroom demonstration. (1st November 2019) - Tél, T; Vincze, M; Jánosi, I M
Abstract: When injecting dye into a vortex, one finds that the dye remains captured around the vortex core over minutes, despite the fact that the vortex (and the dyed region) is strongly time-dependent. According to a recent theory, three-dimensional time-dependent vortices should be defined as rotating, material-holding regions of the fluid. Vortices generated by commercial magnetic stirrers appear to demonstrate this material-holding property. These experiments can be carried out with tap water and food dye in any school. They help make students familiar with the material holding character of vortices. This is a recently understood, rather robust, property, observable also in vortices occurring in nature.